(untitled) (Gaceta Técnica, 2025)
The present investigation aimed to apply different methodologies for assessing seismic vulnerability in an educational institution. The Hypothetical Deductive Method was used, the techniques employed were direct scientific observation and documentary analysis. Data collection was performed using the Benedetti Petrini scale, the Hirosawa scale, the FEMA 154 rapid visual inspection procedure sheet, and Pushover analysis with Etabs. The sample was the San Juan de Chota educational institution, Peru. The results and conclusions obtained using the different methodologies according to the Benedeti Petrini Method, the educational institution presents low vulnerability, according to the Hirosawa method the institution is not vulnerable, according to the FEMA 154 method, it is not vulnerable, on the other hand, according to the Pushover analysis the displacement vs shear curve at the base of the San Juan educational institution for the XX direction is 22,78 cm and a shear of 4684048,31 N. In the case of the YY direction, the maximum displacement is 0,19 cm and a shear of 3420069,19 N, at this moment the structure is in the inelastic regime close to collapse. Finally, it is concluded that applying the methodologies of Hirosawa, Benedetti Petrini, Pushover, the structure of the building applying the four earthquake-resistant evaluation methods, is Not Vulnerable